The Colegio Nacional de Morón (Buenos Aires) and the Malvinas war: a field of tensions. From malvización to desmalvinización (1982-1982) - Paris, Sebastián Federico (Historia y Memoria de la Educación, 2022)
This article focuses on the positions, daily experiences and memories of the members of the educational community of Morón (Buenos Aires) during the war for the Malvinas and its postwar period. To do this, we will resort to the case of the Manuel Dorrego National School, a national public institution in the western suburbs, examining the experiences, meanings and positions between the months of the conflict and the immediate postwar period.